Microbiology of Lactic Acid Fermentation of Eggplant Fruits - ABASSAH-OPPONG, S.; H. OLDHAM, J.; ASIAMAH, I. (Asian Journal of Chemistry, 2010)
The microorganisms responsible for the lactic acid fermentation of eggplant fruits were cultured on the following media: Raka-ray no. 3 agar, orange-serum agar, MRS agar, blood serum agar and sabouraud 2% maltose broth. Pure cultures isolated on the various media were identified using various biochemical tests. The microorganisms which were responsible for the fermentation of the eggplant fruits were Lactobacillus and Leuconostoc. The lactic acid produced, preserved the eggplant fruits for four months when packaged with polyethylene bags.